EVALUASI KEBIJAKAN RELOKASI RUMAH NELAYAN DI BANTARAN SUNGAI BANJIR KANAL TIMUR - Novira Wulandari; Kismartini Kismartini; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The Semarang City Government implemented a residential relocation policy for the Tambakrejo community by preparing Rusunawa Kudu. However, some people choose to stay because Rusunawa Kudu is far from the sea and has the potential to jeopardize the income of fishermen. To that end, the government built row houses. The goal of this research is to assess the relocation policy and examine the elements that support and hinder it. The research method is descriptive qualitative, while the determination of informants uses the purposive sampling method. The findings revealed that an effective relocation policy was defined by a clear knowledge of the objective, as well as clear and easy implementation instructions. The relocation policy in Rusunawa Kudu has been efficient in terms of the ease of the relocation implementation process. However, the relocation of row houses is considered inefficient because additional government efforts are ranging from mediation, communication, to the construction of row houses. The relocation policy of Rusunawa Kudu has the potential to cause population problems even though it has met the need for decent housing. Meanwhile, the relocation of row houses has not provided a maximum solution to the problem seen from the incomplete public facilities. The relocation policy of Rusunawa Kudu and row houses have been considered justice for the people of Tambakrejo. The relocation policy is considered to be appropriate with the distribution of Tambakrejo residents who have been relocated. In the implementation of the settlement relocation policy, there are supporting factors, namely the resources that are used properly, and the powers, interests, and strategies of the actors are applied systematically. The incompatibility of interests that affect the settlement relocation policy is one of the policy's stumbling blocks, as well as the level of compliance and low capture power.